2005
DOI: 10.1262/jrd.51.117
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity of the 5' Upstream Region of the Porcine Glycoprotein Hormone .ALPHA. Subunit Gene

Abstract: Abstract. Gene expression of the porcine glycoprotein hormone α subunit (p-αGSU) was examined in LβT2 cells, which were established from the anterior pituitary lobe of the immortalized transgenic mouse and produce αGSU, and in CHO cells cloned from Chinese hamster ovaries. Expression of the reporter gene fused with p-αGSU gene upstream in LβT2 cells showed that the distal regions -540/-240 and -798/-541 are important for the activation of gene expression. In contrast, the transcriptional activity of the distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…In the distal region, no information on typical regulatory elements has yet been provided, while we recently demonstrated the importance of the distal region of porcine aGSU promoter for the high level and cell-type-specific expression of aGSU gene (Aikawa et al 2005a). Indeed, the study of cis-acting activity revealed two cis-acting elements of Prop-1 located at K1038/K1026 and K942/K928 bp.…”
Section: Discussionmentioning
confidence: 93%
“…In the distal region, no information on typical regulatory elements has yet been provided, while we recently demonstrated the importance of the distal region of porcine aGSU promoter for the high level and cell-type-specific expression of aGSU gene (Aikawa et al 2005a). Indeed, the study of cis-acting activity revealed two cis-acting elements of Prop-1 located at K1038/K1026 and K942/K928 bp.…”
Section: Discussionmentioning
confidence: 93%
“…While the regulation of PGBE with Lhx3 has been well investigated, we recently demonstrated that the distal upstream region plays a role in the remarkable expression of porcine Cga [4]. The region contains many TAAT/ATTA core motifs, a binding element for multiple members of the homeodomain family [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors, Lhx2 [9] and Lhx3 [17] for PGBE, Sf1 for GSE [10], CRE binding protein (Creb) for CRE [13,18] and Gata2 for GATA element [19], participate in cell-type or tissue-specific regulation. Thus, in the proximal region, expression of Cga is controlled by various trans-acting factors through binding to the discrete elements.Recently, we reported a prominent transcription activity of the porcine Cga promoter over the PGBE [4]. The distal region of the porcine Cga promoter shows only moderate sequence homology with that of other mammals.…”
mentioning
confidence: 98%
See 2 more Smart Citations